Mandau Symbolism: Spirituality, Aesthetics, and Social Ethics in Contemporary Dayak Culture - Aquarini Aquarini; Junaidi Junaidi; Lisnawati Lisnawati (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Dayak culture preserves the Mandau as a symbol of spirituality, identity, and morality. However, modernization has transformed its sacred role into a cultural commodity, highlighting the need to reexamine its philosophical and spiritual significance. Objective: This research aims to uncover the symbolic meaning of Mandau in the context of cultural identity, ornamental systems, and its social and ethical functions in contemporary Dayak society. Methods: This study employs an interpretive qualitative approach based on cultural semiotic analysis of literary sources, museum artifacts at the Balanga Museum (Palangka Raya), and secondary ethnographic data from published field studies. Data were analyzed using Barthes' cultural semiotics framework with source triangulation to ensure interpretive validity. Additionally, participatory observation, in-depth interviews with artisans and traditional leaders in Kapuas and Palangka Raya, and artifact analysis at the Balanga Museum were conducted to enrich the ethnographic data. Results: The findings indicate that Mandau functions as a moral and spiritual medium connecting humans, nature, and ancestors; its material structure and ornamental motifs embody the principle of cosmic balance (duality); and its social functions affirm Mandau’s role as a medium for ecological ethics and cultural resilience. Despite functional transformations under globalization, the symbolic meaning of Mandau persists in contemporary Dayak society. Conclusion: Preserving the Mandau requires safeguarding both its physical form and cultural meaning. Collaborative efforts among academics, indigenous communities, and cultural institutions, supported by digital education and documentation, are essential to sustain its ethical and spiritual values across generations.